Religion, reason, and culture in the age of Goethe - Krimmer, Elisabeth, 1967-; Simpson, Patricia Anne, 1958- (Studies in German literature, linguistics, and culture., 2013)
The eighteenth century is usually considered to be a time of increasing secularization in which the primacy of theology was replaced by the authority of reason, yet this endeavor played itself out in a social and political reality that was heavily impacted by religious customs and institutions. 'Religion, Reason, and Culture in the Age of Goethe' investigates how culture in the Age of Goethe shaped and was shaped by a sustained and multifaceted debate about the place of religion and religious difference in politics, philosophy, and culture.